2008
DOI: 10.1016/j.polymer.2008.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Polymer nanotechnology: Nanocomposites

Abstract: a b s t r a c tIn the large field of nanotechnology, polymer matrix based nanocomposites have become a prominent area of current research and development. Exfoliated clay-based nanocomposites have dominated the polymer literature but there are a large number of other significant areas of current and emerging interest. This review will detail the technology involved with exfoliated clay-based nanocomposites and also include other important areas including barrier properties, flammability resistance, biomedical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
1,870
4
78

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 3,036 publications
(1,993 citation statements)
references
References 282 publications
(356 reference statements)
41
1,870
4
78
Order By: Relevance
“…For instance the strain at break of plates decreased from about 1700% for HDPE plates to 380% for LDH-5. The decrease in both tensile strength and strain at break at high nanofiller content, particularly in LDH-5 plates and LDH-3 fiber, has been attributed to the presence of hydrotalcite aggregates, that may behave as defects, and could also reduce the interfacial adhesion between the matrix and the filler [5,47]. Some other indications on the fiber drawing can be evaluated from the mechanical draw ratio " MEC , or the maximum drawability that is defined according to Equation (4): (4) where # b is the strain at break expressed in percentage [13,21].…”
Section: Mechanical Properties Of Plates and Fibersmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance the strain at break of plates decreased from about 1700% for HDPE plates to 380% for LDH-5. The decrease in both tensile strength and strain at break at high nanofiller content, particularly in LDH-5 plates and LDH-3 fiber, has been attributed to the presence of hydrotalcite aggregates, that may behave as defects, and could also reduce the interfacial adhesion between the matrix and the filler [5,47]. Some other indications on the fiber drawing can be evaluated from the mechanical draw ratio " MEC , or the maximum drawability that is defined according to Equation (4): (4) where # b is the strain at break expressed in percentage [13,21].…”
Section: Mechanical Properties Of Plates and Fibersmentioning
confidence: 99%
“…The main reason of this interest lies certainly in the properties of the nanoclay, like high stiffness, and high aspect ratio, that may induce enhancement of various polymer properties (thermal stability, mechanical properties, flame resistance and gas barrier) even with small amount of filler [3,4]. The nano composite materials can exhibit properties over those expected from continuum mechanics predictions, not achieved with larger scale reinforcement [5]. Moreover, nanocomposites can be processed more easily than microcomposites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At one end of this classification scheme are well-ordered and stacked multilayers [41,42]. These consist of polymer chains intercalated between the host layers.…”
Section: Morphologymentioning
confidence: 99%
“…The field of nanotechnology is one of the most popular areas for current research and development in basically all technical disciplines [1]. Ajayan et al [2] reported the first polymernanocomposites using CNTs as a filler.…”
Section: Introductionmentioning
confidence: 99%